Limity zaciągania zobowiązań przez jednostki samorządu terytorialnego w Polsce - stan obecny i proponowane kierunki zmian - Kańduła, Sławomira; Kotlińska, Janina (Limits of incurring Debts by Territorial Government Units in Poland - Present State and Suggested Directions of Changes, 2008)
For several years in Poland it has been a subject of discussion whether or not the state should limit territorial government units' freedom of incurring debts and if yes - how this should be done. Particularly heated debates concern the construction of restrictions limiting the units' level of indebtedness. This study aims at answering several questions. How indebtedness of territorial government units is limited in Poland and in other European countries? What are the disadvantages of restrictions existing presently in Poland? What are the government's proposals of changes in the constructions of restrictions that are in force presently? Will the proposed solutions allow for individual determining the level of indebtedness of particular local government units and therefore will not limit the freedom of incurring debts by "wealthy" local government units but at the same time prevent loss of financial liquidity by financially weaker units? (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 495-506